1987
DOI: 10.3109/02699058709034443
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric interventions with head injured children and adolescents

Abstract: With increasing numbers of surviving head injured children and adolescents, there is a growing need to provide child neuropsychiatric services as a necessary component for their comprehensive rehabilitation. This paper discusses the critical role child psychiatry should have in pediatric head injury rehabilitation and outlines a framework for neuropsychiatric interventions including the use of neuropsychoactive medications. Case examples highlight the principles and practicalities of interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Following a serious TBI a child is at risk of ongoing neuropsychological, behavioural and intellectual problems [11][12][13]. These problems are likely to place additional strain upon his or her parents.…”
Section: Introductionmentioning
confidence: 99%
“…Following a serious TBI a child is at risk of ongoing neuropsychological, behavioural and intellectual problems [11][12][13]. These problems are likely to place additional strain upon his or her parents.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 81% of these brain injuries will be mild, 5% fatal, 6% severe and 8% moderate [6]. For survivors it is likely that there will be intellectual, academic and personality adjustment problems [7]. In a review of the literature, Taylor and Alden [8] concluded that the sequelae of childhood brain injury either remains relatively constant over time post-injury or worsens.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Following a serious TBI it is likely that there will be intellectual, academic and personality adjustment problems. [5][6][7][8] Furthermore, even mild brain injuries can lead to cognitive and behavioural deficits. [9,10] In North Staffordshire a unique register of all children admitted with TBI has been maintained continuously since 1992 presenting an opportunity to accurately establish the incidence of TBI leading to hospital admission within a region with a relatively stable population.…”
Section: Introductionmentioning
confidence: 99%